Additive‐Free, Low‐Temperature Crystallization of Stable α‐FAPbI3 Perovskite. Issue 9 (23rd January 2022) - Du, Tian; Macdonald, Thomas J.; Yang, Ruo Xi; Li, Meng; Jiang, Zhongyao; Mohan, Lokeshwari; Xu, Weidong; Su, Zhenhuang; Gao, Xingyu; Whiteley, Richard; Lin, Chieh‐Ting; Min, Ganghong; et al.
Abstract: Formamidinium lead triiodide (FAPbI3 ) is attractive for photovoltaic devices due to its optimal bandgap at around 1.45 eV and improved thermal stability compared with methylammonium‐based perovskites. Crystallization of phase‐pure α‐FAPbI3 conventionally requires high‐temperature thermal annealing at 150 °C whilst the obtained α‐FAPbI3 is metastable at room temperature. Here, aerosol‐assisted crystallization (AAC) is reported, which converts yellow δ‐FAPbI3 into black α‐FAPbI3 at only 100 °C using precursor solutions containing only lead iodide and formamidinium iodide with no chemical additives. The obtained α‐FAPbI3 exhibits remarkably enhanced stability compared to the 150 °C annealed counterparts, in combination with improvements in film crystallinity and photoluminescence yield. Using X‐ray diffraction, X‐ray scattering, and density functional theory simulation, it is identified that relaxation of residual tensile strains, achieved through the lower annealing temperature and post‐crystallization crystal growth during AAC, is the key factor that facilitates the formation of phase‐stable α‐FAPbI3 . This overcomes the strain‐induced lattice expansion that is known to cause the metastability of α‐FAPbI3 . Accordingly, pure FAPbI3 p–i–n solar cells are reported, facilitated by the low‐temperature (≤100 °C) AAC processing, which demonstrates increases of both power conversion efficiency and operational stability compared to devices fabricated using 150 °C annealed films. Abstract : An aerosol‐assisted crystallization method to prepare high‐quality, pure α‐FAPbI3 films at only 100 °C without chemical additives is reported. Remarkably improved phase stability of the α‐FAPbI3 films and their applications in solar cells are demonstrated. The overriding mechanism of stabilizing α‐FAPbI3 is shown to be relaxation of residual tensile strains in the films.